Re-feeding syndrome and alcoholic cardiomyopathy: A case of interacting diagnoses. Issue 3 (September 2016) - Miller, Robert J.H.; Chew, Derek
Abstract: Re-feeding syndrome is an uncommon clinical entity of fluid and electrolyte disorders that typically occurs after re-initiation of enteral nutrition following prolonged fasting. This disorder can be complicated by left ventricular (LV) dysfunction, arrhythmias, and death. Alcohol abuse and anorexia nervosa are independently associated with similar complications. The interaction between these diagnoses can result in significant, but reversible, LV dysfunction. We present the case of a 69-year-old woman with a history of significant alcohol abuse and anorexia nervosa. The patient was admitted to hospital for the management of re-feeding syndrome, which was complicated by significant LV dysfunction. Her LV function normalized following a combination of electrolyte replacement, re-institution of feeding, and abstinence from alcohol. Re-feeding syndrome, anorexia nervosa, and alcohol abuse are conditions that commonly co-exist. These conditions may have a synergistic relationship, potentially resulting in a profound cardiomyopathy. Careful monitoring and aggressive electrolyte replacement may be helpful in identifying this complication and minimizing its potential harm. <Learning objective: Re-feeding syndrome can be complicated by significant myocardial dysfunction, particularly in patients with a history of alcohol abuse or anorexia nervosa, which independently cause cardiac dysfunction. Physicians should be aware of the risk of new cardiomyopathy in patients with these overlapping diagnoses. We review the case of a patient with these conditions who developed a significant reversible cardiomyopathy managed with re-institution of feeding and electrolyte replacement.>